ORGANIZACIJA RADA RONILAČKOG CENTRA - Veselin Mijajlović; Danilo Mijajlović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Having in mind that the most actual and most perspective export product in Montenegro is touristic service and acti vities regarding sport and recreation as its gre at part; the aim of this work is to in du ce for ming of di ving cen ters on the Mon te ne gro co asts, so that they co uld va lo ri ze spor ti ve, cul tu ral and eco lo gi cal po ten ti als in the pla ce where they work. This work also shows that through ef fective bussiness the consumer appro ach strategy sho uld be de ve lo ped, with aim to pro vi de con fi den ce of the con su mer in the in du stry of spor ti ve/rec re a ti o nal di ving. Goal of this work is to in form fu tu re di ving cen ter fo un ders with the ba sis of the bus si ness in spor ti ve to u rism ge ne rally; to pre pa re them for the job of in struc tor and for the work in cen ter; and to ma ke them mo re fa mi li ar with the va lu es of edu ca ti o nal system and to show them how to use it.